Bluestreak : inside JetBlue, the upstart that rocked an industry - Peterson, Barbara Sturken (New York : Portfolio, 2004)
Describes the airline's evolution from an upstart underdog into a revolutionary company that has transformed the aviation business, discussing its unusual corporate culture, management principles, and innovative approach to business.
Includes bibliographical references (p. 243-251) and index.
Keywords: JetBlue Airways -- History; Airlines -- United States -- History